THE APPLICATION OF VARIOUS TYPES OF SLURRY AND LEVELS OF SOIL WATER CONTENT ON GROWTH AND YIELD OF Indigofera zollingeriana FORAGE - I W., Arista Pratama; Suarna, I W.; Duarsa, M. A. P. (Jurnal Peternakan Tropika, 2017)
This study aimed to determine the growth and yield of Indigofera zollingeriana forage given the different types of slurry and soil water content. This study was conducted at Greenhouse of Tropical Forage Sciences Laboratory, Faculty of Animal Husbandry, Udayana University for 10 weeks. The experiment design used completely randomize design (CRD) factorial pattern with two factors. The first factor was the type of slurry , cattle slurry (S), pig slurry  (B), and cattle bio-slurry (BS), the second factor was soil water content 100% FC (K1), 85% FC (K2), 70% FC (K3), and 55% FC (K4), hence there were 12 treatment combinations. The combination treatments were repeated three times, so there were 36 pots experiment. Variables observed were growth, yield, and growth characteristic. The result showed cattle slurry significantly affect the number of leaves, cattle bio-slurry significantly affect on the total dry weight ratio of forage with root dry weight. Treatment 100% of soil water content was significantly effect on plant height. Treatment 55% of soil water content was significantly effect on the total dry weight ratio of forage with root dry weight. Based on the result of the researchs it can be concluded that cattle bio-slurry tends to provide the distribution of photosynthesis result in proportion to the large leaves and stems rather than to the roots compared to pig slurry and cattle slurry . This study confirmed that Indigofera zollingeriana is a drought resistant species, and there was no interaction between the types of slurry with soil water content in the observed variables (growth, yield, and characteristic). Keywords: Slurry, Bio-Slurry, Soil Water Content, Indigofera z ollingeriana, Growth a nd Yield